2015
DOI: 10.1007/s13337-014-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in gill tissues of White spot syndrome virus infected black tiger shrimp Penaeus monodon by DNA microarray

Abstract: White spot syndrome virus (WSSV) continues to be the most devastating viral pathogen infecting penaeid shrimp the world over. The genome of WSSV has been deciphered and characterized from three geographical isolates and significant progress has been made in developing various molecular diagnostic methods to detect the virus. However, the information on host immune gene response to WSSV pathogenesis is limited. Microarray analysis was carried out as an approach to analyse the gene expression in black tiger shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Various techniques have been applied to study shrimp immune responses to viral infections, including cDNA microarray technology (Aoki et al, 2011; Lu, Hsiao & Wu, 2011; Shekhar et al, 2015) and next generation sequencing (Clavero-Salas et al, 2007; Zeng et al, 2013; Chen et al, 2013). Few researches involving transcriptome study with WSSV infection in shrimp and prawn have been performed to understand the effect of WSSV infection to the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been applied to study shrimp immune responses to viral infections, including cDNA microarray technology (Aoki et al, 2011; Lu, Hsiao & Wu, 2011; Shekhar et al, 2015) and next generation sequencing (Clavero-Salas et al, 2007; Zeng et al, 2013; Chen et al, 2013). Few researches involving transcriptome study with WSSV infection in shrimp and prawn have been performed to understand the effect of WSSV infection to the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…They found that penaeidin-3 isoforms and crustin were over-expressed in hemocytes of WSSV-infected pre-challenged Penaeus vannamei ( García et al, 2009 ). Shekhar et al (2015) utilized DNA microarray technology to explore the genes of host immune responses to WSSV pathogenesis. They found some up- or down-regulated genes during WSSV infection in shrimp ( Shekhar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… Shekhar et al (2015) utilized DNA microarray technology to explore the genes of host immune responses to WSSV pathogenesis. They found some up- or down-regulated genes during WSSV infection in shrimp ( Shekhar et al, 2015 ). Yu et al (2017) found that a combination of single nucleotide polymorphisms in three genes (TRAF6, Cu/Zn SOD, and nLvALF2) were significantly associated with resistance to WSSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods including expressed sequenced tag (EST) 79 , DNA microarray 1014 and proteomic 1519 , have been used to analyse molecular changes during WSSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive investigations of WSSV infection, the mechanisms of WSSV entry and propagation in shrimp have not yet been fully understood. Several methods including expressed sequenced tag (EST) 7 9 , DNA microarray 10 14 and proteomic 15 19 , have been used to analyse molecular changes during WSSV infection.…”
Section: Introductionmentioning
confidence: 99%